ABO Incompatible Renal Transplantation Without Antibody Removal Using Conventional Immunosuppression Alone. Issue 12 (11th November 2014) - Masterson, R.; Hughes, P.; Walker, R. G.; Hogan, C.; Haeusler, M.; Robertson, A. R.; Millar, R.; Suh, N.; Cohney, S. J.
<x xml:space="preserve">Abstract</x> ABO incompatible living donor renal transplantation (ABOi) can achieve outcomes comparable to ABO compatible transplantation (ABOc). However, with the exception of blood group A2 kidneys transplanted into recipients with low titer anti‐A antibody, regimens generally include antibody removal, intensified immunosuppression and splenectomy or rituximab. We now report a series of 20 successful renal transplants across a range of blood group incompatibilities using conventional immunosuppression alone in recipients with low baseline anti‐blood group antibody (ABGAb) titers. Incompatibilities were A1 to O (3), A1 to B (2), A2 to O (2), AB to A (2), AB to B (1), B to A1 (9), B to O (1); titers 1:1 to 1:16 by Ortho. At 36 months, patient and graft survival are 100%. Antibody‐mediated rejection (AbMR) occurred in one patient with thrombophilia and low level donor‐specific anti‐HLA antibody. Four patients experienced cellular rejection (two subclinical), which responded to oral prednisolone. This series demonstrates that selected patients with low titer ABGAb can undergo ABOi with standard immunosuppression alone, suggesting baseline titer as a reliable predictor of AbMR. This reduces morbidity and cost of ABOi for patients with low titer ABGAb and increases the possibility of ABOi from deceased donors.